2020
DOI: 10.3892/ol.2020.11320
|View full text |Cite
|
Sign up to set email alerts
|

TSP‑1 as a novel biological marker of tumor vasculature normalization in colon carcinoma induced by Endostar

Abstract: Blood vessels in tumors often exhibit abnormal morphology and function, which promotes the growth, metastasis and resistance of tumors to conventional therapies. Therefore, vascular normalization is an emerging strategy to enhance the effectiveness of radiotherapy and chemotherapy when used in combination; however, there is a lack of evidence regarding the optimal schedule for the co-administration of anti-angiogenic and chemotherapeutic drugs. Scheduling treatment is important as the period for normalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The platelet thrombin protein THBS1, expressed in the cellular membrane, endoplasmic reticulum and extracellular matrix, plays an important role in platelet aggregation, angiogenesis and the occurrence and development of a variety of malignant tumors (32,33). The expression level and roles of THBS1 vary in different tumor types, where it can play either a stimulatory and inhibitory role.…”
Section: Discussionmentioning
confidence: 99%
“…The platelet thrombin protein THBS1, expressed in the cellular membrane, endoplasmic reticulum and extracellular matrix, plays an important role in platelet aggregation, angiogenesis and the occurrence and development of a variety of malignant tumors (32,33). The expression level and roles of THBS1 vary in different tumor types, where it can play either a stimulatory and inhibitory role.…”
Section: Discussionmentioning
confidence: 99%
“…However, on the basis of further research, antitumor efficacy in both types of tumors was increased by combining exercise with chemotherapy, as a result of exercise-induced shear stress activating calcineurin–NFAT–TSP-1 signaling in ECs and promoting tumor vascular normalization in mouse models ( 108 111 ). Moreover, the level of TSP-1 had been found in recent studies to be usually elevated around normal vessels compared with abnormal vessels, suggesting that TSP-1 may be a marker of vascular normalization ( 112 ).…”
Section: Methods Of Tumor Vascular Normalizationmentioning
confidence: 99%
“…EC proliferation and migration, as well as the expression of VEGF, could be inhibited by an angiogenesis inhibitor, recombinant human endostatin (endostar), which was shown, with recent evidence, to possibly restore vascular homeostasis and induce vascular normalization in some cancer (112,113). However, still unclear is the molecular mechanism, which, in studies, was shown that the Src signaling pathway and matrix metalloproteinase (MMP) might be the mechanism of its action (114,115).…”
Section: Inducing Angiostatic Factorsmentioning
confidence: 99%